2001
DOI: 10.1021/cm001244l
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Derived BN Ceramics: Extensive 11B and 15N Solid-State NMR Study of a Preceramic Polyborazilene

Abstract: Polyborazilene, a precursor for hexagonal boron nitride (h-BN) ceramics, has been extensively characterized by 15N and 11B MAS NMR. The various B and N sites have been identified according to their first neighboring atoms as well as to the second ones in the case of 15N and have also been quantified. This study demonstrates that a suitable choice of NMR techniques together with the use of isotopic enrichment can lead to a large improvement in spectral resolution, which allows better understanding of such compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
101
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 33 publications
(97 reference statements)
12
101
1
Order By: Relevance
“…Hence, either modifying the chemical nature of the used precursor or additivating it with a crystallization promoter would play a key role on the final crystallinity of the ceramic. In that way, as already mentioned in the introduction, the used of PBN as preceramic precursor is particularly relevant [30,50,51,84] since it is prepared through pure borazine that initially displays the expected targeted hexagonal arrangement [85]. Moreover, since the polymer is obtained without any solvent addition, only hydrogen is expected to be lost [25,[86][87][88] and no contaminant is present, whose presence may slow down the crystallization process.…”
Section: Second Strategy: LI 3 N As Crystallization Promotermentioning
confidence: 99%
“…Hence, either modifying the chemical nature of the used precursor or additivating it with a crystallization promoter would play a key role on the final crystallinity of the ceramic. In that way, as already mentioned in the introduction, the used of PBN as preceramic precursor is particularly relevant [30,50,51,84] since it is prepared through pure borazine that initially displays the expected targeted hexagonal arrangement [85]. Moreover, since the polymer is obtained without any solvent addition, only hydrogen is expected to be lost [25,[86][87][88] and no contaminant is present, whose presence may slow down the crystallization process.…”
Section: Second Strategy: LI 3 N As Crystallization Promotermentioning
confidence: 99%
“…9), in agreement with previous reports. 20 In the case of S2, an asymmetric B nucleus peak at À40.5 ppm, between that of GBH and LiBH 4 , was observed, which may be assigned to BH 4 À , induced by GBH and LiBH 4 . Upon heating S2 to 150 C, a principal signal at around À40.4 ppm can be observed, corresponding to residual BH 4 À , and another three signals at À4.6 ppm, À12 ppm, and 15.4 ppm appear, which may be due to the combination of its B-H and N-H, resulting in tetravalent borane nitrogen substances for four and two bound guanidinium units and minor tricoordinated B atoms, respectively.…”
Section: Structure Analysesmentioning
confidence: 91%
“…According to the above analysis, although the intermediate phase is not very clear currently, it is concluded that the dehydrogenation of GBH/LiBH 4 composites is also based on the combination mechanism of H d+ and H dÀ , [11][12][13][14][15]20,23 and that LiBH 4 is able to introduce an effective H dÀ source through the coordination between GBH and LiBH 4 , forming new complexes, enabling the acheivement of the balance of B-H and N-H for the combination. 24 Fig.…”
Section: Structure Analysesmentioning
confidence: 99%
“…23,24 Recently, borazine has been successfully used as a precursor for the synthesis of boron nitride, 25 a widely studied ceramic with valuable properties. [26][27][28][29] The quality of ceramics has been demonstrated to depend considerably on the architecture of the polymer; 30 hence, the choice of characterization tools is critical for monitoring and controlling polymerization and polymer-toceramic conversion. Fazen et al proposed a route to hexagonal boron nitride (h-BN) by thermal polymerization of borazine to form polyborazylene, 25 a polymer composed of linked borazine rings, followed by pyrolysis under an inert atmosphere, to yield the desired product.…”
Section: Introductionmentioning
confidence: 99%
“…This work has been complemented by a characterization study of polyborazylene by Gervais et al using various 11 B and 15 N solid-state NMR experiments. 28 These NMR techniques proved to be very useful in identifying and differentiating the 15 NH x sites (x ) 0-3) and the two types of boron environments, BN 2 H and BN 3 , in polyborazylene.…”
Section: Introductionmentioning
confidence: 99%